2019
DOI: 10.1007/s11769-019-1022-6
|View full text |Cite
|
Sign up to set email alerts
|

Three Types of Spatial Function Zoning in Key Ecological Function Areas Based on Ecological and Economic Coordinated Development: A Case Study of Tacheng Basin, China

Abstract: Three types of spatial function zoning is an effective measure for regional environmental protection and orderly development. For ecological and economic coordinated development, spatial function zones should be divided scientifically to clear its direction of development and protection. Therefore, based on ecological constraints, a beneficial discussion would be about the key ecological function areas adopting the concept of ecological protection restriction and supporting socioeconomic development for spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Yang et al [ 15 ], using the ecological compensation zoning index of cultivated lands and the financial payment model of cultivated lands’ ecology, divided the cultivated lands’ ecological compensation areas in Wuhan. Wang et al [ 16 ], taking the Tarbagatay Basin in the Xinjiang province as an example, constructed an evaluation index system from three aspects of the suitability of ecological protection, urban development, and agricultural production, and divided the ecological, agricultural, and urban space regions of the Tarbagatay Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [ 15 ], using the ecological compensation zoning index of cultivated lands and the financial payment model of cultivated lands’ ecology, divided the cultivated lands’ ecological compensation areas in Wuhan. Wang et al [ 16 ], taking the Tarbagatay Basin in the Xinjiang province as an example, constructed an evaluation index system from three aspects of the suitability of ecological protection, urban development, and agricultural production, and divided the ecological, agricultural, and urban space regions of the Tarbagatay Basin.…”
Section: Introductionmentioning
confidence: 99%
“…This method of analytic hierarchy process calculates the weight of each element by ordering in single level and whole system of each evaluation index and judges the matrix consistency test during the sorting operation to avoid one-sidedness. When the consistency ratio is less than 0.1, the consistency check of the judgement matrix is acceptable; otherwise, the judgement matrix does not meet the consistency requirement and corresponding judgement matrix must be revised until the results are tested with consistency [43].…”
Section: The Methods Of the Weighted Averagementioning
confidence: 99%
“…It was found that the management plan for the protected area includes supply and cultural services, but almost no regulation services [30]. Wang et al established an evaluation index system from three aspects: Ecological protection, agricultural production, and urban development suitability, and divided the Xinjiang Tacheng Basin into ecological, agricultural, and urban space [31]. However, these divisions are suitable at the regional-scale, whereas more detailed classification is needed at the county-scale.…”
Section: Integrated Ecosystem Service Supply and The Ecosystem Management Model Of Consumptionmentioning
confidence: 99%